FPGA Interconnect Topologies Exploration. (10th September 2009) - Marrakchi, Zied; Mrabet, Hayder; Farooq, Umer; Mehrez, Habib
Abstract : This paper presents an improved interconnect network for Tree-based FPGA architecture that unifies two unidirectional programmable networks. New tools are developed to place and route the largest benchmark circuits, where different optimization techniques are used to get an optimized architecture. The effect of variation in LUT and cluster size on the area, performance, and power of the Tree-based architecture is analyzed. Experimental results show that an architecture with LUT size 4 and arity size 4 is the most efficient in terms of area and static power dissipation, whereas the architectures with higher LUT and cluster size are efficient in terms of performance. We also show that unifying a Mesh with this Tree topology leads to an architecture which has good layout scalability and better interconnect efficiency compared to VPR-style Mesh.